Formulation of moringa leaf powder (Moringa oleifera) and red ginger powder (Zingiber officinale var. Rubrum) on the chemical characteristics of herbal drink - Rahman, Suburi; Dwiani, Afe; Nurmiati, Nurmiati; Firmansyah, Firmansyah (Jurnal Agrotek Ummat, 2024)
Herbal drinks are one of the most popular drinks for consumption because of health benefits. Herbal drinks are drinks that made from plants (dry form) such as flowers, fruits, seeds, stems, rhizomes, leaves and so on. Moringa leaves are plants whose leaf parts are often processed into herbal drinks. The high antioxidant in moringa leaves can improve the function of herbal drinks, but moringa leaves has an unpleasant aroma. Therefore, red ginger is used to improve the sensory and chemical quality of herbal drink. The purpose of this study was to obtain the best proportion of the main ingredients on the chemical quality of herbal drink products. This study used a completely randomized design (CRD), with 7 treatments of material proportions, namely JK0 (Moringa leaf powder 0%: red ginger powder 100%), JK1 (Moringa leaf powder 15%: red ginger powder 85%), JK2 (Moringa leaf powder 35%: 65% red ginger powder), JK3 (50% moringa leaf powder: 50% red ginger powder), JK4 (65% moringa leaf powder: 35% red ginger powder), JK5 (85% moringa leaf powder: 15% red ginger powder) and JK6 (100% moringa leaf powder: 0% red ginger powder). Each treatment was repeated 3 times and 21 experimental units were obtained. Based on the results of the analysis of variance and Tukey's further test (5%), it is known that the proportion of moringa leaf powder and red ginger powder produces a significant effect on chemical quality (water content, pH and antioxidant activity) in herbal drink. The best treatment for the proportion of moringa leaf powder and red ginger powder was produced by JK5 (85% moringa leaf powder: 15% red ginger powder) with chemical quality, like water content of 4.56% (suitable SNI 4324-2014), pH with a value of 5.16 and antioxidant activity with a value of 65.96%.